Disability in Aging People: Functioning Difficulties and Infrastructural Barriers - Khanal, Kashi Nath (Journal of Development Review, 2023)
Disability is the physical, mental and psychological condition that prevents an individual to perform common type of day-to-day activities, and creates significant barrier in social participation. It includes health loss, status loss, and social loss. Disability snatches individual’s functioning capacities. Structural barriers restrict people with disabilities from full and effective participation in society. Disability is not a personal problem; it is shaped by the larger socio-cultural, geo-political and economic context of a nation. Also, there are perfect parallels between disability and aging. As people age, they experience multiple chronic illnesses. Thus, both the disability and aging require prompt service and extra care. Owing to the unfavorable socio-cultural environment, aging and disable people tend to keep their stories within without sharing them to others. Disabled people do not consider them as weak and inept, rather the negative perceptions of disability relegate people with disability to the background. Also, the contribution of currently-aging population in their past working-age deserves to be marked. Since ageing crosscuts disability, it becomes fundamental to analyze the functioning condition of ageing and disabled people, and their access to physical infrastructure. This paper concludes that the problems faced by aging and disabled people could be lessened if a friendly infrastructure is built.